Effect of Addition of Different Levels of Commercial Inoculant of Lactic Acid Bacteria And Soluble Sugars on Fermentation of Wheat Straw Silage (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
This study was conducted to investigate the effect of addition of different levels of commercial inoculant of lactic acid Bacteria (Ecosyl), 0, 1×105 and  1×106  cfu/g wet material and 4 levels of debis as a source of soluble sugars, 4, 6, 8 and 10% on dry matter (DM) basis on fermentation of wheat straw silage. Urea was added to all samples at rate of 1%. Results revealed that addition of inoculant improved (P